A Solution‐Processed Resonance Host for Highly Efficient Electrophosphorescent Devices with Extremely Low Efficiency Roll‐off. (30th September 2015) - Tao, Ye; Guo, Xin; Hao, Lin; Chen, Runfeng; Li, Huanhuan; Chen, Yuehua; Zhang, Xinwen; Lai, Wenyong; Huang, Wei
Abstract : Solution‐processible N–P=O resonance‐host molecules are applied successfully in spin‐coated phosphorescent light‐emitting diodes (PHOLEDs) to selectively and self‐adaptively tune the electrical properties for balanced charge transportation. The resonance‐molecule‐hosted PHOLEDs exhibit a high maximum quantum efficiency of 16.5% and a low efficiency roll‐off down to 0.7%, highlighting the significant progress of these solution‐processed PHOLEDs with high efficiency and flat efficiency roll‐off achieved simultaneously.